(untitled) (Development Service Industry Management, 2025)
The article is devoted to a detailed study of the problems and prospects of investing in human capital in wartime, which becomes extremely relevant for ensuring the stability and sustainable development of the country in conflict conditions. In modern war conditions, when social structures, in particular the education and health care system, are destroyed, and access to necessary resources is reduced, the preservation and development of human potential is a key factor for restoring the economy and ensuring social stability. The article provides a comprehensive analysis of the main challenges faced by countries in a state of war, in particular limited access to quality education, a significant reduction in medical services, the outflow of qualified personnel and a high level of psychological trauma among the population. The study also focuses on the impact of war on the main components of human capital, including the need to preserve and develop the workforce, optimize the education system, health rehabilitation, and psychological support. Special attention is paid to innovative approaches to investing in human capital in conditions of limited resources. In particular, it proposes methods for implementing remote technologies in education and health care, which will minimize losses from infrastructure destruction. In addition, it considers the importance of international assistance and cooperation for the restoration of critical sectors, such as health care and educational programs. Among the proposed measures, retraining programs are also highlighted to ensure the adaptation of the workforce to new conditions, as well as the creation of effective psychological support mechanisms for people affected by the war. The recommendations are aimed at creating conditions for the preservation and development of labor resources, increasing labor productivity, and ensuring the rapid restoration of socio-economic infrastructure after the end of the conflict.